2016
DOI: 10.1007/s10853-016-0360-3
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the acidic–basic properties by Zn-substitution in Mg–Al hydrotalcites as optimal catalysts for the aldol condensation reaction

Abstract: ratios were prepared by co-precipitation in super-saturated conditions, followed by thermal decomposition at 500°C. The synthesized materials were evaluated as catalysts for the self-condensation of octanal in order to establish structure-tofunctionality properties of the prepared materials. The presence of zinc affects the structural and textural properties of the as-synthesized hydrotalcites and derived mixed oxides, and provokes a remarkable modification on the acidicbasic properties of the materials as stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 44 publications
(63 reference statements)
0
26
0
Order By: Relevance
“…The strength of basic sites can be tuned by changing the Mg/Al ratio and the calcination temperature. It was reported that the presence of less basic cations than Mg 2+ , such as Al 3+ , could decrease the basic strength of LDH samples . In our experiment, the increase in Mg/Al ratio enables to increase the amount of basic sites of calcined samples due to the decrease in Lewis acidic sites.…”
Section: Resultsmentioning
confidence: 99%
“…The strength of basic sites can be tuned by changing the Mg/Al ratio and the calcination temperature. It was reported that the presence of less basic cations than Mg 2+ , such as Al 3+ , could decrease the basic strength of LDH samples . In our experiment, the increase in Mg/Al ratio enables to increase the amount of basic sites of calcined samples due to the decrease in Lewis acidic sites.…”
Section: Resultsmentioning
confidence: 99%
“…The strength and density of the acid sites were determined using ammonia temperature-programmed desorption (NH 3 -TPD) analysis (Figure 4b). The NH 3 -TPD profile has two overlapping curves, where the first peak at around 110 • C could be due to the desorption of residual NH 3 weakly bonded to the surface of the catalyst, and could be attributed to the existence of Brønsted acid sites on the surface of catalysts, created by the existence of OHgroups [28]; and the second peak at around 190 • C, might be caused by further desorption of stronger bonded NH 3 species from the Lewis acid sites ascribed to the presence of Al 3+ − O 2− − Mg 2+ species in the structure of the mixed oxides and containing the Al 3+ cations mainly in octahedral sites [28,29].…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Aldol condensation of aldehydes can be catalyzed by acid, base or acid-base bifunctional catalysts [19] [20]. In aldol condensation catalyzed by base (Scheme 1), an enolate is formed by the abstraction of the α-hydrogen of the carbonyl compound with the help of a base.…”
Section: Mechanism Of Aldol Condensationmentioning
confidence: 99%
“…Strong bases are usually used for condensation of ketone with large steric hindrance. Acid catalysts are often used in aldol condensation reactions [19] [20]. Commonly used acid catalysts include (VO 2 P 2 O 7 , VOHPO 4 ), niobate and MFI zeolite.…”
Section: Mechanism Of Aldol Condensationmentioning
confidence: 99%